간세포암과 동반된 중복암의 임상병리학적 특징 - 최동호(Dongho Choi); 김한준(Hanjoon Kim); 이경근(Kyeong Geun Lee); 박훤겸(Hwon Kyum Park); 권오정(Oh Jung Kwon); 이광수(Kwang Soo Lee) (Annals of surgical treatment and research, 2003)
Purpose: Multiple primary cancers are not a rare disease. The clinicopathologic characteristics of a hepatocellular carcinoma with extrahepatic malignancies, have not been identified. To address these points, the clinical data of patients with a hepatocellular carcinoma, with extrahepatic malignancies, treated with surgical resections at our hospital, were retrospectively reviewed. Methods: We reviewed the clinical records of ten hepatocellular carcinoma patients, with extrahepatic malignancies, who had undergone an operation between January, 1986 and December, 2002 at the Hanyang University Hospital. Results: 10 patients were comprised of 9 males and 1 female, with a mean age of 58.6 years, ranging from 34 to 75. There were 9 stomach cancers and 1 rectal cancer extrahepatic malignancies associated with the hepatocellular carcinomas. Four of these were synchronous type and six were metachronous type. The treatments used for the HCCs were: 1 extended right lobectomy, 6 right lobectomies, 1 each of a TAE with RFTA, a segmentectomy with RFTA, and a segmentectomy. The operations for the extrahepatic malignancies included 1 low anterior resection, for the rectal cancer and 9 subtotal gastrectomies, for the stomach cancers. During the mean follow up time of 66.1 months, five patients survived and five died. Conclusion: Patients who have a hepatocellular carcinoma, associated with extrahepatic malignancies, have been treated with aggressive operations and combination therapies. Stomach cancer is the most common extrahepatic malignancy associated with a hepatocellular carcinoma. (J Korean Surg Soc 2003;64:487-492) KCI Citation Count: 0